Análise da presença de vírus em alho semente da segunda e quarta gerações, produzidos por termoterapia e cultura de tecido - Oliveira, Milena Leite De [UNESP]; Nardini, João Paulo Calore [UNESP]; Marchi, Bruno Rossito De [UNESP]; Mituti, Tatiana [UNESP]; Bampi, Daiana [UNESP]; Pavan, Marcelo Agenor [UNESP]; Krause-sakate, Renate [UNESP] (Grupo Paulista de Fitopatologia, 2014)
The garlic (Allium sativum L.) can be naturally infected by a complex of filamentous viruses belonging to the genera Potyvirus, Carlavirus and Allexivirus. Accumulation of these viruses occurs especially by vegetative propagation through cloves. As the cultivated garlic plant does not produce true seed worldwide, virus-free plants can only be obtained by tissue culture of stem apices and thermotherapy. Using these techniques, garlic seeds were produced at the School of Agricultural Sciences - UNESP, Botucatu, and evaluated by RT-PCR for the presence of potyvirus, carlavirus and allexivirus. In the second generation of microcloves propagated in a greenhouse, 6.6% infection was detected, only by allexivirus. In the fourth generation, however, there was 60% incidence by allexivirus, 35% by potyvirus and all negative by carlavirus. The high rate of infection by allexivirus may be related to the greater difficulty of removing the species of viruses belonging to this genus, as observed by other authors, and also based on the infection and transmission of the virus by the mite, Aceria tulipae, during the storage of bulbs from one year to the other. The garlic at the fourth generation corresponds to cloves weighed less than 1 gram and not selected for commercial multiplication. Selection for the size of cloves has a positive effect on the choice of cloves with lower rates of viral infection, as the technique of thermotherapy and tissue culture do not eliminate the virus completely. Results also emphasize the need of fumigation for the garlic seed stored from one year to the other in order to prevent the transmission of allexivirus during storage.

O alho (Allium sativum L.) pode estar naturalmente infectado por um complexo de vírus filamentosos pertencentes aos gêneros Potyvirus, Carlavirus e Allexivirus. O acúmulo destes vírus se dá, principalmente, pela sua propagação vegetativa através dos bulbilhos. Como a planta de alho cultivada não produz semente verdadeira em todo o mundo, a única forma de se obter plantas livres de vírus se dá pela cultura de tecidos dos ápices caulinares e termoterapia. Utilizando estas técnicas, alhos sementes foram produzidos na FCA- UNESP de Botucatu e avaliados via RT-PCR para a presença de potyvirus, carlavirus e allexivirus. Na segunda geração dos microbulbilhos propagados em casa de vegetação, 6,6% de infecção foi verificada por allexivirus. Já na quarta geração foi observada incidência de 60% com allexivirus, 35% com potyvirus e todas foram negativas para carlavirus. A alta taxa de infecção por allexivirus pode estar relacionada à maior dificuldade de remoção de espécies de vírus pertencentes a este gênero, como também já observado por outros autores, pela infecção e transmissão de vírus pelo ácaro, Aceriatulipae, durante o armazenamento dos bulbos de um ano a outro. O alho na quarta geração corresponde a bulbilhos com peso inferior a 1 grama e que não haviam sido selecionados para multiplicação comercial. A seleção para tamanho do bulbilho tem efeito positivo na escolha de bulbilhos com menores taxas de infecção por vírus, já que a técnica de termoterapia e cultura de tecidos não elimina totalmente os vírus. Os resultados também enfatizam a necessidade de se realizar fumigação no alho semente armazenado de um ano a outro a fim de evitar a transmissão de allexivirus durante o armazenamento.
Analysis of the presence of viruses in garlic seed produced by thermotherapy culture and tissue
Keywords: Allium sativum L.; Potyvirus; Carlavirus e Allexivirus; Allium sativum L.; Potyvirus; Carlavirus and Allexivirus